2015
DOI: 10.1002/app.42818
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fermentation residues on the thermal, structural, and rheological properties of polyhydroxy(butyrate‐co‐valerate) produced from cheese whey and olive oil mill wastewater

Abstract: On the use of tris(nonylphenyl) phosphite as a chain extender in melt-blended poly(hydroxybutyrate-co-hydroxyvalerate)/ clay nanocomposites: Morphology, thermal stability, and mechanical properties Interaction and quantification of thymol in active PLA-based materials containing natural fibers I. S. M. A. Tawakkal, M.ABSTRACT: The effects of recovered residues on the characteristics of polyhydroxy(butyrate-co-valerate) (PHBV) produced from mixed microbial cultures (MMCs) fed with cheese whey, olive oil mill wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
(81 reference statements)
4
14
0
Order By: Relevance
“…The thermal transition observed in the first heating curve at 60 °C (Fig. (A)) – hereafter T g2 – has previously been reported for samples stored at room temperature, and has been attributed to the glass transition temperature of the rigid amorphous fraction (RAF) . The RAF is formed even after very short periods (< 24 h) of storage at temperatures above the glass transition temperature of the mobile amorphous fraction .…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The thermal transition observed in the first heating curve at 60 °C (Fig. (A)) – hereafter T g2 – has previously been reported for samples stored at room temperature, and has been attributed to the glass transition temperature of the rigid amorphous fraction (RAF) . The RAF is formed even after very short periods (< 24 h) of storage at temperatures above the glass transition temperature of the mobile amorphous fraction .…”
Section: Resultsmentioning
confidence: 52%
“…Several studies have led to similar observations in regards to the effect of the biomass residues and the purification methods on the thermal stability. 11,13,28,37,38 In addition, it has been reported that some impurities can behave as plasticisers, enhancing the mechanical properties of PHA, 28,38 which emphasize the importance of testing other properties besides the PHA purity when evaluating purification methods. The presence of impurities should only be considered detrimental when affecting negatively the PHA properties and applicability.…”
Section: Wileyonlinelibrarycom/jctbmentioning
confidence: 99%
“…The FP7 EcoBioCAP project 6 demonstrated the feasibility, using food industry by-products as feedstock (olive wastewater or cheese whey) and mixed natural microbial cultures (MMC), of lab scale production of a P(HB-co-HV) with a HV fraction (in the range of 10–25%) higher than the current commercial grade (3941). This higher HV fraction induces some polymer structural changes that can be advantageous to its processing and conversion into packaging (42, 43). Higher HV contents could be achieved using Volatile Fatty Acids (VFAs precursors) with a high propionic acid content.…”
Section: Solutions and Tools To Align With The Principles Of Circularmentioning
confidence: 99%
“…The extent to 781 which a product of consistent quality can be delivered with wastewater as feedstock has not been 782 proven or refuted even if there is speculation that methods to achieve consistency of product quality 783 will be a challenge in real world implementations. The thermal, structural and rheological properties 784 of PHA produced by MMC have been studied in PHA produced from cheese whey permeate [101] 785 and PHA produced from cheese whey and olive oil mill wastewaters [102]. In addition, Hilliou et 786 al.…”
Section: Digested 714mentioning
confidence: 99%
“…In addition, Hilliou et 786 al. (2016) [102] assessed the effects of the recovered PHA residues on properties that were relevant 787 for the conversion of polymers into packages. It has been suggested that lipids that are co-recovered 788 with PHA from biomass can be used to advantage as compounded agents [103].…”
Section: Digested 714mentioning
confidence: 99%